Manipulation and Equity-Based Compensation - Peng, Lin; Röell, Ailsa (American Economic Review, 2008)
Economists have long argued that a strong linkage between compensation and performance is essential for resolving the agency problem created by the separation of ownership and control. In particular Michael C. Jensen and Kevin J. Murphy (1990) were very influential in giving impetus to the view that such incentives were in need of strengthening. Compared to accounting benchmarks, the stock price is more forward looking, and it is responsive to all value-relevant information, including informal and unverifiable items of news. This makes stock and/or option awards an important part of optimal incentives, and constitutes a primary reason for seeking a public listing, as argued by Bengt Holmstrom and Jean Tirole (1993). Until recently, however, theories of optimal executive compensation have generally ignored the possibility that the stock price can be manipulated or falsified. It is becoming increasingly clear that this is an important issue. In a spate of recent scandals, companies have misled the investing public by vastly overstating their profitability and prospects, and substantive restatements of company accounts have become increasingly commonplace. A growing body of empirical evidence suggests that executive pay in its current form may be at least in part responsible. Recent studies finding a link between unusual movements in performance measures (such as accounting yardsticks and publicly disclosed price-sensitive information) and compensation include Daniel Bergstresser and Thomas Philippon (2006), Natasha Burns and Simi Kedia (2006), and Peng and Roell (forthcoming). Thus, the benefits of stock-based incentives should be weighed against their side effects. This paper models optimal executive compensation in a setting where managers are in a position to influence the public perception of Manipulation and Equity-Based Compensation